Structural and Energy Processes in Electrically Exploded Conductors; Russian Physics Journal; Vol. 45, № 12 - Ilyin A. P. Aleksandr Petrovich; Nazarenko O. B. Olga Bronislavovna; Tikhonov D. V. Dmitry Vladimirovich; Ushakov V. Ya. Vasily Yakovlevich; Yablunovskii G. V. (2002, 2002)
Режим доступа: по договору с организацией-держателем ресурса